ANALISIS PENGARUH MANAJEMEN PIUTANG USAHA, HUTANG, PENDAPATAN DAN BIAYA TERHADAP ARUS KAS: Analysis of the Effect of Accounts Receivable, Debt, Revenue, and Expenses on Cash Flow - Fariantin, Erviva; Arsane, I Nengah; Setiowati, Elvina (Ganec Swara, 2026)
This study was conducted at KSP Madani NTB for the 2016–2025 period, with cash flow as the dependent variable and accounts receivable, debt, revenue, and expenses as the independent variables. Cash flow showed an increasing trend, although it experienced slight fluctuations during several periods. The increase in cash flow was not always in line with the increase in revenue, but was more influenced by cost efficiency and effective management of accounts receivable. Overall, the research data used indicate that cost control and effective accounts receivable management are the main factors in maintaining cash flow stability. The purpose of this study was to determine whether accounts receivable, debt, revenue, and expenses have a significant effect on cash flow, both partially and simultaneously. This study employed a quantitative method with a sample size of 10. The data analysis techniques used included descriptive statistical tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and coefficient of determination tests. The test results showed that partially, accounts receivable, debt, and revenue had no significant effect on cash flow, while expenses had a significant effect on cash flow. Simultaneously, accounts receivable, debt, revenue, and expenses showed a significant effect on cash flow